Community nursing and antibiotic stewardship: the importance of communication and training. (2nd July 2019) - Chater, Angel; Courtenay, Molly
Abstract : Antimicrobial stewardship (using antimicrobials responsibly) can reduce the risk of antimicrobial resistance (AMR). Many health professionals identify themselves as 'antibiotic guardians', but patient expectations, time constraints, and a lack of confidence or underdeveloped communication skills can influence decisions to prescribe. Nurse prescribers have an important role to play in antibiotic stewardship, and their numbers continue to grow. While nurse prescribers welcome this extension to their traditional role, they are often faced with barriers to antibiotic stewardship activities. These barriers may relate to their Capability (knowledge/skill), Opportunity (norms of practice, influence of patients, environmental factors), and Motivation (attitudes and beliefs, concern over outcome, emotion and habit) [COM-B]. Education, training and enablement can help to overcome these barriers, and the development of knowledge, confidence and effective communication skills should be of priority. Further, communication skills can help nurse prescribers understand patient expectations, with the use of open-ended questions, active listening and creation of a patient-centred consultation that leads to a mutually agreed end goal and way forward.